Characterization of flow rate and Heat Loss in Heating, Ventilation and Air Conditioning (HVAC) Duct System for Office Building - Mat Hassan, Nik Normunira; Leman, A. M.; Mohamed Noor Zafarullah, Muhammad Alif; Salleh, Zuliazura; Rahman, K. A.; Madon, Rais Hanizam; Muzarpar, S.; Zamree, A. R. Shayfull (2021)
A building is an assemblage that is firmly attached to the ground and provides the performance of human activities and need to be considered in the daily operation in that building. The improvements in building performance are focused on improving the energy efficiency of buildings. This is approach by designing heating, ventilation and air conditioning (HVAC) duct system due to one of the most utilized energy in maintaining building performance and environment. The objectives of this research is to calculate the air (CFM) supply in office building, to characterize the velocity and head loss in a round and rectangular HVAC ducting system at various duct thickness and to optimize the thickness of the duct in HVAC system according to ASHRAE Standard. The increasing of velocity in duct system shows the increasing of head loss. The round duct design gives the lowest velocity and head loss in HVAC system approximately around 9.35% as compared to rectangular duct at 0.06 inches thickness. Hence, the trends of the head loss and duct thickness has influenced in reducing noise in HVAC duct system in order to select the best design concepts which is round shape design.